2009
DOI: 10.1016/j.pepi.2009.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the perovskite structure and possibility of the transition to the post-perovskite structure in CaSiO3, FeSiO3, MnSiO3 and CoSiO3

Abstract: High pressure and high temperature experiments on CaSiO 3 , FeSiO 3 , MnSiO 3 and CoSiO 3 using a laser-heated diamond anvil cell combined with synchrotron X-ray diffraction were conducted to explore the perovskite structure of these compounds and the transition to the post-perovskite structure. The experimental results revealed that MnSiO 3 has a perovskite structure from relatively low pressure (ca. 20 GPa) similarly to CaSiO 3 , while the stable forms of FeSiO 3 and CoSiO 3 are mixtures of mono-oxide (NaCl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…As already mentioned, experimental studies have reported that the Pv and pPv phases are not stable in FeSiO 3 . Instead, a mixture of FeO (B1 phase) and a high-pressure SiO 2 phase was found in experiments covering a wide pressure range up to GPa (Fujino et al 2009). In this study, we have shown that FeGeO 3 behaves similarly and breaks down into GeO 2 + FeO at least up to 1.27 Mbars.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…As already mentioned, experimental studies have reported that the Pv and pPv phases are not stable in FeSiO 3 . Instead, a mixture of FeO (B1 phase) and a high-pressure SiO 2 phase was found in experiments covering a wide pressure range up to GPa (Fujino et al 2009). In this study, we have shown that FeGeO 3 behaves similarly and breaks down into GeO 2 + FeO at least up to 1.27 Mbars.…”
Section: Discussionmentioning
confidence: 56%
“…Further understanding of the behavior of FeGeO3 relative to other analogs can by obtain by consideration of the the Goldschmidt diagram. This type of diagram has been commonly used to predict the stability of the perovskite and post-perovskite structures in ABO 3 compounds (Goldschmidt 1926;Hattori et al 1999;Fujino et al 2009;Tateno et al 2010) (Figure 6). The Goldschmidt tolerance factor, t, can be used to assess the potential stability of the two phases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some theoretical studies also suggested that the solid solutions of the CaSiO 3 -MgSiO 3 perovskite would be unexpected (e.g., Vitos et al 2006;Jung and Schmidt 2011). Conversely, Fujino et al (2009) suggested that some amount of FeSiO 3 may be incorporated into CaSiO 3 perovskite; however, no quantitative data have been available so far. Thus, CaSiO 3 perovskite has been often treated as a pure phase in the lower mantle.…”
Section: Introductionmentioning
confidence: 99%